Impact of Seizure Recurrence on 1-Year Functional Outcome and Mortality in Patients With Poststroke Epilepsy. (26th July 2022) - Yoshimura, Hajime; Tanaka, Tomotaka; Fukuma, Kazuki; Matsubara, Soichiro; Motoyama, Rie; Mizobuchi, Masahiro; Matsuki, Takayuki; Manabe, Yasuhiro; Suzuki, Junichiro; Kobayashi, Katsuya; Shimotake, Akihiro; Nishimura, Kunihiro; et al.
Abstract : Background and Objectives: The functional outcome and mortality of patients with poststroke epilepsy (PSE) have not been assessed in a prospective study. Previous reports have suggested that patients with PSE may suffer from prolonged functional deterioration after a seizure. In this study, we prospectively investigated the functional outcome and mortality of patients with PSE and analyzed the effect of seizure recurrence on the outcomes. Methods: This is part of the Prognosis of Post-Stroke Epilepsy study, a multicenter, prospective observational cohort study, where 392 patients with PSE (at least 1 unprovoked seizure more than 7 days after the onset of the last symptomatic stroke) were followed for at least 1 year at 8 hospitals in Japan. This study included only PSE patients with a first-ever seizure and assessed their functional decline and mortality at 1 year. Functional decline was defined as an increase in modified Rankin Scale (mRS) score at 1 year compared with baseline, excluding death. The associations between the seizure recurrence and the outcomes were analyzed statistically. Results: A total of 211 patients (median age of 75 years; median mRS score of 3) were identified. At 1 year, 50 patients (23.7%) experienced seizure recurrence. Regarding outcomes, 25 patients (11.8%) demonstrated functional decline and 20 (9.5%) had died. Most patients died of pneumonia or cardiac disease (7 patients each), and no known causes of death were directly related to recurrent seizures. Seizure recurrence was significantly associated with functional decline (odds ratio [OR] 2.96, 95% CI 1.25–7.03, p = 0.01), even after adjusting for potential confounders (adjusted OR 3.26, 95% CI 1.27–8.36, p = 0.01), but not with mortality (OR 0.79, 95% CI 0.25–2.48, p = 0.68). Moreover, there was a significant trend where patients with more recurrent seizures were more likely to have functional decline (8.7%, 20.6%, and 28.6% in none, 1, and 2 or more recurrent seizures, respectively; p = 0.006). Discussion: One-year functional outcome and mortality of patients with PSE were poor. Seizure recurrence was significantly associated with functional outcome, but not with mortality. Further studies are needed to ascertain whether early and adequate antiseizure treatment can prevent the functional deterioration of patients with PSE.